2011
DOI: 10.1109/tbme.2011.2158647
|View full text |Cite
|
Sign up to set email alerts
|

Scalp EEG Acquisition in a Low-Noise Environment: A Quantitative Assessment

Abstract: This pilot study investigates effects of an ultra shielded capsule at the low-noise underground laboratory (LSBB), Rustrel, France, when used to acquire scalp electroencephalogram (EEG). Analysis of EEG recordings from three volunteers confirms that clean EEG signals can be acquired in the LSBB capsule without the need for notch filtering. In addition, using different setups for acquiring EEG in the capsule, statistical analysis of power spectral densities based on a geodesic distance measure reveals that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…Although having slightly higher values in LSBB, backward counting-rest ratios are mainly distributed around one in both environments, suggesting that gamma band may not be significantly involved in continuous counting tasks. We have found this to be the case also in a previous study [6]. On the other hand, matching-rest ratios are mainly greater than one in both environments, and their values are higher in LSBB at temporal and occipital regions of the brain.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although having slightly higher values in LSBB, backward counting-rest ratios are mainly distributed around one in both environments, suggesting that gamma band may not be significantly involved in continuous counting tasks. We have found this to be the case also in a previous study [6]. On the other hand, matching-rest ratios are mainly greater than one in both environments, and their values are higher in LSBB at temporal and occipital regions of the brain.…”
Section: Discussionsupporting
confidence: 88%
“…In a previous study, we have shown that EEG signals acquired in LSBB are free from electromagnetic interference and can be acquired and analyzed without the need for notch filtering with battery-powered EEG equipment [6,7]. This facilitates examination of gamma-band EEG signals acquired in the LSBB while searching for functionally significant high-frequency EEG correlates which would otherwise be obscured by common filters of high-frequency electromagnetic noise.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In two previous studies [1], [2] we have demonstrated the potential of the ultra-low noise shielded capsule at the heart of LSBB is an ideal environment for acquiring ultra-high, wideband electroencephalographic (EEG) signals without the need of filtering. The EEG has proven to be a useful information source in the analysis of brain activity, neural plasticity, and the diagnosis of various neurological disorders, as well as the development of intelligent brain-computer interfaces (BCIs).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] Complexity reduction and fast convergence of the noise cancelation algorithm have remained a topic of intense research. This is because of the fact that with increase in the data transmission rate increases the order of filter.…”
Section: Introductionmentioning
confidence: 99%